Hubungan antara Kedalaman Permukaan Air Tanah dengan Salinitas di Pesisir Pantai Kungkai Baru serta Penggunaan Model Discovery Learning - Sutijo Joko Sudiro; Muchammad Farid; Eko Swistoro (University of Bengkulu, 2018)
ABSTRACT [Relationship between Groundwater Surface Depth with Salinity at the Coast of New Kungkai Beach and its Implementation on Discovery Learning Model]. The aims of this study were 1) to describe the relationship between groundwater surface depth with salinity in the coastal areas of new kungkai beach of Seluma, and 2) to determine the improvement of learning outcomes (cognitive) of high ability students, moderate and low by using discovery learning model on the concept of static fluid in class X computer and network engineering at SMK Negeri 3 Seluma. This research was a quasi experimental research with one groups pretest-posttest design. The results showed: 1) The relationship between depth with salinity has a value of 0.6478 with a significance level of 0.001 (<0.05); 2) Learning with discovery learning model can improve student learning outcomes on cognitive aspects (knowledge). Increased cognitive results can be seen from the average value of the initial test, the final test and the average value of gain in the class x Tkj is high-ability groups are at high criteria with a value of 0.75 gain in the group is in the criteria medium with the value of gain 0,52 and in the low group were in moderate criteria with a gain value of 0.44. There is a difference in learning outcomes between the high, medium and low groups. The difference is shown by Fcount > Ftable (4.04 > 3.35) with a significance level of 5%. Keywords: Groundwater surface depth; salinity; discovery learning model; SMKN 3 Seluma.